Glutathione and associated antioxidant systems in protein energy malnutrition: Results of a study in nigeria - Becker, Katja; Leichsenring, Michael; Gana, Lawan; Bremer, Hans J.; Schirmer, Rolf Heiner (Free radical biology and medicine, 1995)
Marasmus and kwashiorkor are manifestations of protein energy malnutrition. The pathophysiology of these disorders is poorly understood. We studied a number of blood antioxidants [glucose-6-phosphate dehydrogenase (G6PDH), glutathione reductase (GR) and its cofactor flavin adenine dinucleotide (FAD), the tripeptide glutathione as the major nonprotein thiol], serum albumin, and retinol-binding protein in 12 children suffering from kwashiorkor with all classical symptoms, in 13 patients with clinically severe marasmus, in 19 marasmic but active children, and in 23 controls. Significant changes were observed for erythrocyte glutathione and correspondingly for nonprotein thiols in whole blood (0.72 ± 0.29 mM thiols in controls, 0.50 ± 0.22 mM in marasmus, 0.35 ± 0.23 mM in severe marasmus, and 0.22 ± 0.13 mM in kwashiorkor). These differences were paralleled by a decrease in serum albumin concentration so that the molar ratio of nonprotein thiols/albumin had an average value of approximately 1.5 in all groups. The erythrocyte glutathione-reducing system, represented by G6PDH and glutathione reductase, showed only slight differences among the four groups of children; the supposition that kwashiorkor occurs predominantly in children with aberrant G6PDH could not be substantiated. Unexpectedly, erythrocyte FAD, an index of riboflavin status, was normal in most malnourished patients. Discussed is the prospect of administering glutathione in kwashiorkor patients.
Elektronische Reproduktion der Druck-Ausgabe 28. Dezember 1999
Gesehen am 29.05.2024